2018
DOI: 10.1016/j.arth.2017.11.029
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Irrigation and Debridement in Total Knee Arthroplasty Periprosthetic Joint Infection: Treatment Failure Is High

Abstract: Background In total knee arthroplasty (TKA) periprosthetic joint infection (PJI), irrigation debridement (I&D) with component retention is a treatment option with a wide variation in reported failure rates. The purpose of this study was to determine failure rates, outcomes, and factors that predict failure in I&D for TKA PJI. Methods A multicenter observational study of patients with a TKA PJI and subsequently undergoing an I&D with retention of components was conducted. The primary outcome was failure rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 31 publications
0
84
0
2
Order By: Relevance
“…Similarly, the type of cement and dosage of antibiotic in two-stage revisions was not standardized, nor were the diagnostic criteria for confirming eradication and clearance for reimplantation. Although the lack of treatment standardization in PJI is not unique to our study [29][30][31][32] , we acknowledge that this makes interpretation of a single variable (the intravenous antibiotic) difficult to interpret with regard to treatment outcome. The formalization of PJI consensus criteria has improved treatment standardization in our institution over the past year and we plan to re-evaluate daptomycin performance on more recent cases treated by a smaller group of high volume revision surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the type of cement and dosage of antibiotic in two-stage revisions was not standardized, nor were the diagnostic criteria for confirming eradication and clearance for reimplantation. Although the lack of treatment standardization in PJI is not unique to our study [29][30][31][32] , we acknowledge that this makes interpretation of a single variable (the intravenous antibiotic) difficult to interpret with regard to treatment outcome. The formalization of PJI consensus criteria has improved treatment standardization in our institution over the past year and we plan to re-evaluate daptomycin performance on more recent cases treated by a smaller group of high volume revision surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a range of pathogenesis from simple, superficial abscesses to life threatening systemic sepsis, the outcomes of these disease processes resolve over a limited time period. An exception is surgical infection where chronic infections can develop over an extended period of time and biofilm formation plays an important physiologic role (5, 11). Regulation of growth, biofilm formation, and antibiotic tolerance could have important roles of bacteria physiology in this disease state.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroplasty is a common surgical procedure, and the most common reason for failure is infection, termed periprosthetic joint infection (3, 4). S. aureus periprosthetic joint infection can be culture negative for prolonged periods (5, 6), has high failure rates above 50% once treatment is initiated (5), and a 5-year mortality of 20% (79), higher than many common cancers (10). Similar to other surgical implant associated infections, the challenge in treating this disease involves the ability of S. aureus to develop a chronic biofilm associated infection tolerant to antibiotics (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…However, the success in controlling the infection varies from 31% to 100%. 13,[14][15][16][17] Although the term DAIR is not used in megaprosthesis infection papers, the outcome of debridement and implant retention in this group of patients has been very poor. Jeys et al reported that there were 68 patients of 136 patients treated with local debridement.…”
Section: Discussionmentioning
confidence: 99%